Population Study of the Golden Chicken Fern (Cibotium barometz (L.) J. Sm. in Riau Province, Sumatra - Titien Ngatinem Praptosuwiryo; Dwi Murti Puspitaningtyas; Didit Okta Pribadi; Rugayah Rugayah (Journal of Tropical Life Science, 2017)
Cibotium barometz (L.) J.Sm. (Cibotiaceae) is an important export commodity for both traditional and mod-ern medicine. Populations of this species in several countries have decreased rapidly due to the uncontrolled collection of the rhizome parts for medicinal purposes. Since 1976, this species has been included in Appendix II of the Convention on International Trade in Endangered Species (CITES). This means that no export is allowed without a prior permit issued by the CITES committee. In order to utilize an endangered species sustainably, the global NDF (Non-Detriments Finding) system is applied for determining annual quotas. Therefore, monitoring and updating the inventory of C. barometz in its natural habitat should be carried out annually. A population study of C. barometz carried out in 2011 in Riau Province, Sumatra, is reported here. The aims of the study were: 1) to inventory C. barometz and determine its variation in Riau Province, Suma-tra, 2) to study the distribution and ecology of C. barometz, and 3) to assess the population size of this spe-cies by using random search methodology incorporating belt line transects. Two variants of C. barometz are recognized; they are the golden yellow and golden brown variants. C. barometz is distributed in eight loca-tions of Kampar District of Riau Province, in the secondary forest and rubber agroforest between 80 m and 600 m above sea level (asl). This species grows well in open to partially opened areas of secondary forest and rubber plantation in hills with a range of slope between 30° and 90°, with a relatively high humidity, 60 – 90%, in acid to nearly neutral soil, with a range of soil fertility from very poor to very humus rich soil. The average population density determined in our study was 20 plants per 100 square meter. The highest popula-tion size was in the secondary forest of Bukit Kuda Beban at 590 – 600 m asl., viz. 9405 plants with a popula-tion density of 47 plants per 100 square meter.